GR_GERICHTE ZK2 2022 24 vom 9. November 2022 , Beschwerde gegen StA, Einspracheentscheide - GR Gerichte (2022)
gesellschaftsrechtliche Verantwortlichkeit | Berufung OR AG/andere Handelsgesellschaft/Genossenschaft